Second Tour of the Theosophist Jinarajadasa to Latin America, 1938. An analysis of his conferences and other essays - Mejía Burgos, Otto German (2018)
This article describes the close relationship between theosophical societies, public opinion, Salvadorian Government and world theosophy’s figures. These sectors in spite of their political differences, were interconnected under the same esoteric tendency: theosophy. We also, explain the Salvadorian newspapers’ reaction upon Jinarajadasa’s second visit to Latin America and the Caribbean, analyzing some of his conferences as well as different articles published on the occasion of such a transcendental event.